2021
DOI: 10.1177/15357597211029517
|View full text |Cite
|
Sign up to set email alerts
|

TRAPing Seizures in the Striatum

Abstract: Epub ahead of print. PMID: 33730155.There are no detailed descriptions of neuronal circuit active during frontal lobe motor seizures. Using activity reporter mice, local field potential recordings, tissue clearing, viral tracing, and super-resolution microscopy, we found neuronal activation after focal motor to bilateral tonic-clonic seizures in the striatum, globus pallidus externus, subthalamic nucleus, substantia nigra pars reticulata and neurons of the indirect pathway. Seizures preferentially activated do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 52 , 53 , 54 , 55 It has been suggested that overt clinical seizures may thus depend on both an epileptogenic focus and a compromised inhibitory control mechanism. 44 This hypothesis of inhibitory control to suppress or even prevent seizures has seen renewed interest, 56 as it may help explain why patients with epilepsy do not continuously seize, 57 why only some seizures generalize, 58 , 59 and why seizures stop. 47 However, where this inhibitory control network might be localized in the human brain has remained a debate and whether it plays a role in epileptogenesis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 53 , 54 , 55 It has been suggested that overt clinical seizures may thus depend on both an epileptogenic focus and a compromised inhibitory control mechanism. 44 This hypothesis of inhibitory control to suppress or even prevent seizures has seen renewed interest, 56 as it may help explain why patients with epilepsy do not continuously seize, 57 why only some seizures generalize, 58 , 59 and why seizures stop. 47 However, where this inhibitory control network might be localized in the human brain has remained a debate and whether it plays a role in epileptogenesis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…9 Many previous studies have demonstrated electrographic activation of the basal ganglia structures during seizures. [10][11][12][13][14][15][16] Drug experiments such as GABAergic inhibition of the SNR 14 or pharmacological activation of the striatum 17 exhibited anticonvulsant effects, demonstrating that the basal ganglia modulate seizures. Yet, direct cellular evidence of basal ganglia circuit activation was lacking.…”
Section: Frontal Lobe Onset Seizuresmentioning
confidence: 99%